Composition of Flavonoids in the Petals of Freesia and Prediction of Four Novel Transcription Factors Involving in Freesia Flavonoid Pathway - Zhu, Jiayi; Guo, Xueying; Li, Xin; Tang, Dongqin (Frontiers in Plant Science, 2021)
Freesia hybrida is rich in flower colors with beautiful flower shapes and pleasant aroma. Flavonoids are vital to the color formation of its flowers. In this study, five Freesia cultivars with different flower colors were used to study on the level of accumulation of their flavonoids and expression of flavonoid-related genes and further explore new novel transcription factor (TF). Ultra-high-performance liquid chromatography and VION ion mobility quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF-MS) were used to determine the flavonoids. Combined with transcriptome sequencing technology, the molecular mechanism of the flavonoid metabolism difference in Freesia was revealed. A total of 10 anthoxanthin components and 12 anthocyanin components were detected using UPLC-Q-TOF-MS. All six common anthocyanin aglycones in high plants, including cyanidin, delphinidin, petunidin, peonidin, malvidin, and pelargonidin, were detected in Freesia at first time in this study. In orange, yellow, and white cultivars, anthoxanthins gradually decreased with the opening of the petals, while in red and purple cultivars, anthoxanthins first increased and then decreased. No anthocyanin was detected in yellow and white cultivars, while anthocyanins increased with the opening of the petals and reached their maximum at the flowering stage (S3) in other three cultivars. The correlation analysis revealed that the color of Freesia petals was closely related to the composition and content of anthoxanthins and anthocyanins. Petals of five cultivars at S3 were then selected for transcriptome sequencing by using the Illumina Hiseq 4000 platform, and a total of 100,539 unigenes were obtained. There were totally 5,162 differentially expressed genes (DEGs) when the four colored cultivars were compared with the white cultivar at S3. Comparing all DEGs with gene ontology (GO), KEGG, and Pfam databases, it was found that the genes involved in the flavonoid biosynthesis pathway were significantly different. In addition, AP2, WRKY, and bHLH TF families ranked the top three among all differently expressed TFs in all DEGs. Quantitative real-time PCR (qRT-PCR) technology was used to analyze the expression patterns of the structural genes of flavonoid biosynthesis pathway in Freesia. The results showed that metabolic process was affected significantly by structural genes in this pathway, such as CHS1, CHI2, DFR1, ANS1, 3GT1, and FLS1. Cluster analysis was performed by using all annotated WRKY and AP2 TFs and the above structural genes based on their relatively expression. Four novel candidate TFs of WRKY and AP2 family were screened. Their spatiotemporal expression patterns revealed that these four novel TFs may participate in the regulation of the flavonoid biosynthesis, thus controlling its color formation in Freesia petals.